TINJAUAN PADMASARI DI MERAJAN PASEK GELGEL DESA SERASON PENEBEL TABANAN - Putu Gde Ery Suardana; I Ketut Watu Asihawan (Universitas Dwijendra, 2016)
Bali island of a thousand temples so we often hear in the community, the gods worshiped by his people in a temple in Bali, one of the means of worship that is â€œPadmasariâ€ which has three parts or ornament (structure). Based on the location of â€œPadmasariâ€ have different functions. Usually we can find the front yard of the house, at the fork in the road or seemingly hauntedplace. This paper is a case study using observation, interview, litelatur study with the data scattered in various places. The research goal for know the function form and structureâ€Padmasariâ€Keywords : Form, structure